2010
DOI: 10.1029/2009ja015026
|View full text |Cite
|
Sign up to set email alerts
|

VLF observations of ionospheric disturbances in association with TLEs from the EuroSprite‐2007 campaign

Abstract: Two Very Low Frequency (VLF) AWESOME remote sensing systems located at Algiers, Algeria (36.45°N, 3.28°E) and Sebha, Libya (27.02°N, 14.26°E) monitor VLF signal perturbations for evidence of ionospheric disturbances. During the EuroSprite‐2007 campaign a number of Transient Luminous Events (TLEs) were captured over the Mediterranean Sea by cameras at Pic du Midi (42.94°N, 0.14°E) and at Centre de Recherches Atmosphériques (CRA) in southwestern France (43.13°N, 0.37°E). The cameras observations are compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 26 publications
1
41
0
Order By: Relevance
“…From early/fast events and sprite observations in the USA, Marshall et al (2006) reported that only a very small subset (9 out 250) of sprites shows characteristics of the VLF wide-angle scattering from the sprite body, and that all such cases correspond to multiple sprites or horizontally expansive sprites. Early/fast events associated with wide-angle scatterings have been reported under the EuroSprite-2007(NaitAmor et al, 2007. The narrowangle scattering of VLF signals has also been reported to be associated from smoother and larger regions of the enhanced electron density and wideangle scattering associated with columns of enhanced ionization due to strong sprites .…”
Section: Resultsmentioning
confidence: 92%
“…From early/fast events and sprite observations in the USA, Marshall et al (2006) reported that only a very small subset (9 out 250) of sprites shows characteristics of the VLF wide-angle scattering from the sprite body, and that all such cases correspond to multiple sprites or horizontally expansive sprites. Early/fast events associated with wide-angle scatterings have been reported under the EuroSprite-2007(NaitAmor et al, 2007. The narrowangle scattering of VLF signals has also been reported to be associated from smoother and larger regions of the enhanced electron density and wideangle scattering associated with columns of enhanced ionization due to strong sprites .…”
Section: Resultsmentioning
confidence: 92%
“…This, combined with the fact that an event may not be detectable by all links that have similar GCPs, means that there are more reasons involved in LORE generation and/or VLF detection, such as the path geometry, as discussed by Nait Amor et al . []. This observation indicates that the requirement for a large peak current intensity and a short distance of discharge location to GCP is a strong contributing factor in the observation of LORE events, but this by itself is not a sufficient criterion for LORE detection.…”
Section: Resultsmentioning
confidence: 99%
“…The amplitude steps are ~1.0 dB, but in general, they can range from a fraction of decibels to several decibels. The perturbation amplitudes were not analyzed here, as they are affected in a complex way by many factors [ Marshall et al ., ] including the causative peak current intensity and the distance of discharge location relative to a VLF link GCP [ NaitAmor et al ., ], the VLF transmitter signal characteristics (e.g., power and frequency), complex waveguide modal propagation and scattering geometry effects [ Poulsen et al ., ], and ambient ionospheric conditions, whose effects on the signal amplitude are not easily quantified.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Kotovsky and Moore [] point out that a large number of sprite halos are triggered by negative cloud‐to‐ground strokes and suggest a different mechanism. As if the lightning properties are not sufficiently complicated, NaitAmor et al [, ] suggest that the distance between the disturbed region to both the transmitter and the receiver, as well as the scattering angle, may be a more important factor than the parameters of the lightning, for both ordinary early and LORE events. These two studies included observations from multiple transmitters and receivers for the same event, which appeared very differently in VLF data.…”
Section: Introductionmentioning
confidence: 99%